Conflict, settlement, and the shadow of the future - Michael McBride; Stergios Skaperdas (Center for Economic Studies and ifo Institute (CESifo), 2009)
In many instances of potential violent or non-violent conflict the future strategic positions of adversaries are very different when there is open conflict than when there is settlement. In such environments we show that, as the future becomes more important, open conflict becomes more likely than settlement. We demonstrate the theoretical robustness of this finding, discuss its applicability in war, litigation, and other settings, and test it in a laboratory experiment. We find that subjects are more likely to engage in risky conflict as the future becomes more important.
Keywords: C72; C91; D01; D74; 330; conflict; litigation; property rights; folk theorem